Technology and the environment in sub-Saharan Africa : emerging trends in the Nigerian manufacturing industry - Adeoti, John O. (Aldershot, Hampshire, England ; Burlington, VT, USA : Ashgate, 2002)
John Adeoti critically examines whether the stimulus-response notion of environmental politics functions as the primary motivation for the adoption of pollution control technologies in Sub-Saharan Africa.
"An earlier version of this book is a Ph.D. dissertation at the Faculty of Economics and Business Administration, Maastricht University, The Netherlands, under the title: Technology investment in pollution control in Sub-Saharan Africa: the case of the Nigerian manufacturing industry"--P. opp. t.p.
Includes bibliographical references (p. [244]-258) and index.
oif 16/09/15
Loan
Keywords: Pollution -- Africa, Sub-Saharan.; Environmental policy -- Africa, Sub-Saharan.; Manufacturing industries -- Environmental aspects -- Nigeria